The Influence of the Picture and Picture Learning Model Assisted by Audio Visual Media on Students' Social Sciences Learning Outcomes - Indarsi, Hilda; Lukman, Lukman; Jamaludin, Jamaludin (PT. Riset Press International, 2024)
Education is capable create source Power more human​ quality Because own good knowledge and skills.​ The picture and picture learning model is a learning model that uses picture as a learning medium supported by audio-visual media and will support enhancement results Study student. Formulation problem is There is the influence of the picture and picture model assisted by audio visual media on results studying social studies in class V at SDN Powaru. Research purposes Know the influence of the picture and picture model assisted by audio visual media on results studying social studies in class V at SDN Powaru. Type of research used in study This is type study quantitative. Method experiment is method study quantitative used​ For know the influence of the independent variable ( treatment ) on the dependent variable ( outcome ) in controlled conditions.​ A form of pre- experimental design was used is a one-group pretest- posttest design. Research result Implementation learning using the picture and picture learning model assisted by audio-visual media. Before start study first stage​ a pretest was carried out in the form of tests on students class V at SDN Powaru District​ South Bungku District. Morowali Central Sulawesi Province. Pretest was carried out to results learn social studies students class V before they given treatment form picture and picture learning assisted by audio visual media.